Níveis de gravidade do trauma e predição de sobrevida em vítimas de acidente de trânsito - Carrapateira, Leonardo da Cruz (2017)
Traffic accidents have become one of the main causes of morbidity and mortality, with a high rate of deaths and survivors incapacitated worldwide. Campo Grande currently occupies one of the ten most violent capitals in transit. As a result of these traumas suffered by traffic accidents trigger, depending on the severity of the injury suffered in traffic accidents, there is a greater or lesser probability of survival. Thus, evaluation systems were set up to estimate the severity of the lesion and its probability of survival. The objective of the present study was to analyze the severity levels of trauma and prediction of survival in patients victims of traffic accidents in Campo Grande - MS. A total of 196 victims of traffic accidents hospitalized in the orthopedic sector of the Beneficial Society of Campo Grande - Santa Casa participated in the study. Indices were used to evaluate the severity of the trauma of the lesions and to calculate the probability of survival due to the traffic accident. Of the 196 victims studied, 70.4% were male, aged 18-25 years 40.3%, where the situation of the victim at the time of the accident affected mainly motorcyclists / passengers 67.3% and day of the week that occurred The accident prevailed weekend, Friday and Saturday respectively 24% and 23.5%. The severity of the trauma severity score (ISS) analyzed in the victims presented a score between 9 and 15 in 47% of the victims, equivalent to mild injuries. While the probability of survival analyzed by the Revised Trauma Score (RTS) index showed a score of 91-96% in 56.1% of the victims. The probability of survival analyzed by the TRISS severity index presented scores of 98 to 99% in 85.2% of the victims, meaning a high degree of survival to the traumatic event. The trauma severity indexes showed a high survival probability score in the study participants.